Respuesta :
[tex] \frac{2}{ \sqrt{3} - 1 } \\ \frac{2}{ \sqrt{3 } - 1} \times \frac{ \sqrt{3} + 1}{ \sqrt{3} + 1} \\ \frac{2 \times ( \sqrt{3} + 1)}{( \sqrt{3} - 1)( \sqrt{3 } + 1) } = \frac{2 \sqrt{3} + 2}{( \sqrt{3} )^{2} - {1}^{2} } \\ \frac{2 \sqrt{3} + 2 }{3 - 1} = \frac{2 \sqrt{3} + 2 }{2} = \frac{2( \sqrt{3} + 1)}{2} \\ \sqrt{3 } + 1 = 1.732 +1 = 2.732[/tex]
Or
[tex] \frac{2}{ \sqrt{3 - 1} } \\ \frac{2}{ \sqrt{2} } \times \frac{ \sqrt{2} }{ \sqrt{2} } = \frac{2 \sqrt{2} }{( \sqrt{2} ) ^{2} } = \frac{2 \sqrt{2} }{2} \\ \sqrt{2} = 1.4142[/tex]
I hope I helped you^_^